Original articleβ-amyloid (Aβ) deposition in cognitively normal brain, dementia with Lewy bodies, and Alzheimer’s disease: a study using principal components analysis - A. Armstrong, Richard (Folia Neuropathologica, 2012)
The densities of diffuse, primitive, and classic β-amyloid (Aβ) deposits were studied in the temporal lobe in cognitively normal brain, dementia with Lewy bodies (DLB), familial Alzheimer’s disease (FAD), and sporadic AD (SAD). Principal components analysis (PCA) was used to determine whether there were distinct differences between groups or whether Aβ pathology was more continuously distributed from group to group. Three principal components (PC) were extracted from the data accounting for 56% of the total variance. Plots of cases in relation to the PC did not result in distinct groups but suggested overlap in Aβ deposition between the groups. In addition, there were linear correlations between the densities of Aβ deposits and the distribution of the cases along the PC in specific brain regions suggesting continuous variation from group to group. PC1 was associated with the degree of maturation of Aβ deposits, PC2 with differences between FAD and SAD, and PC3 with the degree of spread of Aβ pathology into the hippocampus. Apolipoprotein E (APOE) genotype was not associated with variation in Aβ deposition between cases. PCA may be a useful method of studying the pathological interface between closely related neurodegenerative disorders.